Hydrocarbon synthesis, its position to-day and aspects of application to South African conditions - Roediger, L. K. E.(Ludwig Konrad Ernst) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1947.